A systematic approach to the dilemma between flood vulnerability and resilience - Review and concepts - Tri, Hoang Cong; Hens, Luc; Thien Phuoc, Pham Minh; Hung, Nguyen Thanh; Phuong, Tran Ha (Vietnam Journal of Science and Technology, 2017)
The nature of "vulnerability" is that it not only exists when elements at risk are exposed to flood, but also hides in interactions between environmental, social and economic factors before the flood incident. While ecological resilience reflects the dynamic characteristics of resources, ecological vulnerability systematically describing aspects of stress was less researched. This paper develops a concept, modeling dynamic interactions between stress and resources taking into account of context, space, time, and stakeholder involvements, to provide direct causes and solutions for flood risk management. The paper reviews three major schools of thought concerning (i) vulnerability and resilience are two sides of the same coin, (ii) resilience is a part of vulnerability, and (iii) they are two separated concepts with some overlaps. Limitations of the schools of thought were recognized based on four main criteria: (i) vulnerability and resilience must reflect all social, economic and environmental aspects, (ii) they exist regardless of hazards, (iii) they are processes than outcomes, and (iv) they entail multiple objectives. Inspired by the flipping coin and separated concepts, a new framework has been developed. It acknowledges from outstanding points of the two that vulnerability and resilience are normalized as stress and resources of the same coin. Additionally, they can generate positive and/or negative outcomes. Therefore, their relationships are complex because resources, defined by stakeholders, may prevent system changes and consequently amplify stress. Depending on the ratio between stress and resources, a system can be characterized as a 'resistant', or a 'creative' regime. If incremental disturbances exceed the recovery threshold as defined by the available data and the stakeholders, the system might change regime. Decision makers can take advantage of this framework to prepare appropriate resources that increase the resilience of the community and anticipate adverse effects for incoming floods.